Pengaruh Brand Image, Country Of Origin Dan Product Knowledge Terhadap Keputusan Pembelian Smartphone Merek Oppo Di Counter Alibaba Batu - Apsari, Ismi Yulinda Ayu; Salim, Muhammad Agus; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research was carried out with the aim of finding out and analyzing the influence of brand image,country of origin, product knowledge purchasing decisions for Oppo brand smartphone at Alibaba Batu Malang. The samples in this research used purposive sampling and research with a quantitative approach. The sample in this study was 85 respondents. Data collection techniques by distributing questionnaires. data analysis method uses validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, hypothesis test multiple linear regresion analysis,f tests,t tests and coefficient of determination. The analysis tool used is IBM SPSS 25. Based on the research results, it is known that the t test result show that brand image significanly influences purchasing decisions. The significanse value ofthe f test states that together ,brand image,country of origin and product knowledge have a signivican impact.significant to purchasing decisions. Keywords: Brand image, Country of origin, Product knowledge, Purchasing decisions